Groover's principles of modern manufacturing materials, processes, and systems - Groover, Mikell P. (John Wiley & Sons, 2017)
Groover's Principles of Modern Manufacturing is designed for a first course or two-course sequence in Manufacturing at the junior level in Mechanical, Industrial, and Manufacturing Engineering curricula.